Impact of switching to tenofovir alafenamide on weight gain as compared to maintaining a non-tenofovir alafenamide containing regimen. Issue 34 (27th August 2021) - Darnell, Julia; Jain, Sonia; Sun, Xiaoying; Qin, Huifang; Reynolds, Timothy; Karris, Maile Young; Hill, Lucas A.
Abstract : Abstract: Evaluate the impact of switching to an anti-retroviral regimen containing tenofovir alafenamide (TAF) on weight and the development of metabolic complications compared to remaining on a non-TAF containing regimen. Single-center retrospective case-control study. We evaluated people living with human immunodeficiency virus (PLWH) who were on an anti-retroviral regimen not containing TAF and were switched to a regimen containing TAF between January 1, 2016 and September 30, 2018. The control group included PLWH on a TAF free regimen throughout the study period. The primary outcome was change in weight from baseline to 12 months postswitch. Secondary outcomes included percent change in weight, change in body mass index (BMI), change in BMI class, and new diagnoses of diabetes, hypertension, and hyperlipidemia (HLD) during the study period. PLWH switched to TAF (n = 446) demonstrated significantly greater mean increase in weight compared to the control group (n = 162) (1.97 vs 0.88 kg, P = .01), however the effect was only seen in those switched from tenofovir disoproxil fumarate. Those that switched to TAF also had a significantly higher percent increase in weight, increase in BMI, and BMI class. We observed a higher rate of new diagnosis of HLD in the control group compared to the TAF switch group during the study period. PLWH switched to TAF had greater increases in weight after 1 year as compared to those continuing on a TAF free regimen. However, this did not translate to higher rates of obesity related illnesses such as diabetes, hypertension, and HLD during the follow up period.